Secretaries Talk: Sexuality, Power and Work - Maroney, Heather Jon (Labour / Le Travail, 1991)
The article reviews the book, "Secretaries Talk: Sexuality, Power and Work," by Rosemary Pringle.
Keywords: BOOKS – Reviews; Nonfiction; PRINGLE; Rosemary; SECRETARIES Talk: Sexuality; Power & Work (Book); Work environment